PENGARUH LEVERAGE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA INDUSTRI KESEHATAN DI BEI PERIODE 2019 – 2023 - Daniel Daniel; Revi Arfamaini (J-MACC, 2025)
This research was conducted with the aim of knowing the effect of leverage as measured by the Debt to Asset Ratio (DAR), and dividend policy as measured by the Debt to Equity ratio (DER), Dividend Yield, Dividend Payout Ratio and Dividend per Share on the measured company value. with the Price Earning Ratio (PER) in the health industry listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. This type of research is quantitative with secondary data through health industry financial reports listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The population in this study was 33 companies. The sampling technique used purposive sampling to obtain 11 companies. The statistical tests used are descriptive statistics, classical assumption tests, coefficient of determination, multiple regression analysis and partial t test with results: 1) Hypothesis test results show that DAR (Leverage) has no effect on PER (Company Value). 2) DER (Leverage) has no effect on PER (Company Value). 3) Dividend Yield (Dividend Policy) has no effect on PER (Company Value). 4) Dividend Payout Ratio (DPR) (Dividend Policy) has an effect on PER (Company Value). 5) Dividend per Share (DPS) (Dividend Policy) has an effect on PER (Company Value).